Yiwei decoction promotes apoptosis of gastric cancer cells through spleen-derived exosomes - Chen, Yingzhi; Li, Yu; Wu, Yue; Chen, Shiyong; Jin, Xiaoming; Chen, Xuan; Fei, Baoying; Xue, Xiaomin; Wu, Renzhao; Chai, Kequn (Frontiers in Pharmacology, 2023)
Yiwei decoction (YWD) is a formula of traditional Chinese medicine (TCM) that is clinically effective for the prevention and treatment of gastric cancer recurrence and metastasis. According to the theory of TCM, YWD tonifies the body and strengthens the body’s resistance to gastric cancer recurrence and metastasis potentially via the immune regulation of the spleen. The aims of the present study were to investigate whether YWD-treated spleen-derived exosomes in rats inhibit the proliferation of tumor cells, to elucidate the anticancer effects of YWD, and to provide evidence supporting the use of YWD as a new clinical treatment for gastric cancer. Spleen-derived exosomes were obtained by ultracentrifugation and identified by transmission electron microscopy, nanoparticle tracking analysis, and western blot analysis. The location of the exosomes in tumor cells was then determined by immunofluorescence staining. After tumor cells were treated with different concentrations of exosomes, the effect of exosomes on cell proliferation was determined by cell counting kit 8 (CCK8) and colony formation assays. Tumor cell apoptosis was detected by flow cytometry. Particle analysis and western blot analysis identified the material extracted from spleen tissue supernatant as exosomes. Immunofluorescence staining showed that spleen-derived exosomes were taken up by HGC-27 cells, and the CCK8 assay confirmed that the relative tumor inhibition rate of YWD-treated spleen-derived exosomes in the 30 μg/mL reached 70.78% compared to control exosomes in the 30 μg/mL (p < 0.05). Compared to control exosomes in the 30 μg/mL, the colony formation assay indicated that YWD-treated spleen-derived exosomes in the 30 μg/mL colonies have decreased by 99.03% (p < 0.01). Moreover, flow cytometry analysis showed that treatment with YWD-treated exosomes in the 30 μg/mL increased the apoptosis rate to 43.27%, which was significantly higher than that of the control group in the 30 μg/mL (25.91%) (p < 0.05). In conclusion, spleen-derived exosomes from YWD-treated animals inhibit the proliferation of HGC-27 cells via inducing apoptosis, suggesting that spleen-derived exosomes are involved in mediating the antitumor effect of YWD. These results demonstrated a novel exosome-mediated anticancer effect of YWD as a TCM formula, thereby supporting the use of YWD-treated exosomes as a new approach for the clinical treatment of gastric cancer.